(untitled) (Педагогіка вищої та середньої школи, 2004)
Account of the age psychological particularities of the development schoolboys at period of early adolescence and particularities component composition to educational activity pupils in their senior year with standpoint of the organizations of the checking the knowledge in condition larval-oriented education on example of the test tasks are analyzed in article.